2011
DOI: 10.1002/hup.1188
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine in the treatment of adolescents with attention deficit/hyperactivity disorder: an open-label study

Abstract: The results of this open-label study suggest a promise of duloxetine in the treatment of youth with ADHD. Further controlled studies with larger samples are required to evaluate the efficacy of duloxetine in children and adolescents with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…This issue has been studied in recent research that showed positive effects of a monotherapy with fluoxetine in patients with ADHD on aggression, inattention, and depressive symptoms (38). Moreover, an open‐label study in a small sample of adolescents with ADHD using duloxetine showed promising initial results and positive effects on inattention, hyperactivity, and oppositional behaviour (39). This finding is closely related to comorbid conduct problems, which are frequently observed in patients with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…This issue has been studied in recent research that showed positive effects of a monotherapy with fluoxetine in patients with ADHD on aggression, inattention, and depressive symptoms (38). Moreover, an open‐label study in a small sample of adolescents with ADHD using duloxetine showed promising initial results and positive effects on inattention, hyperactivity, and oppositional behaviour (39). This finding is closely related to comorbid conduct problems, which are frequently observed in patients with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…In another open trial, duloxetine was given to 13 adolescents with ADHD. A significant reduction in ADHD symptoms measured by CPRS-R was observed from week four (32).…”
Section: Discussionmentioning
confidence: 88%
“…Duloxetine (repurposed emerging) was tested [42] in a singlearm trial on adolescents, lasting 6 weeks. Duloxetine dose was 60 mg/d.…”
Section: Serotonin-norepinephrine Reuptake Inhibitors (Snris)mentioning
confidence: 99%